Pteridophyta Herbarium Based On Science, Technology, engineering, and Mathematic In Plantae Material in Senior High School (Universitas Negeri Semarang, 2020)
Observation result according to five senior high schools in Semarang was found out that Plantae material was taught with the conceptual method by using limited learning media, such as handout book and students’ worksheet. Plantae material should be taught contextually by using a real object, so the students could find the concept. Contextual learning can be done by using a potential environment. One of the areas with abundant biological diversity especially ferns, located in Bukit Gentong, Kendal Regency. This diversity can be used to be learning media such as herbarium. Herbarium becomes one of the alternative learning media because it is easy to be brought, practical and effective. STEM-based arranged for herbarium media because it can be more interesting than other bases. This research’s objectives are 1) to develop Pteridophyta herbarium based on STEM to accomplish basic competency of 3.8 and 4.8, 2) to analyze Pteridophyta herbarium validity a learning media, and 3) to analyze the effectiveness of Pteridophyta herbarium media concerning to students’ marks. This method of this research used Research and Development by the ADDIE model. Research data consist of data validity and herbarium effectiveness, analyzed by quantitative descriptive. The result of this research show 1) Pteridophyta herbarium based on STEM media was appropriate with the basic competency of 3.8 and 4.8, 2) Pteridophyta herbarium media was very valid and suitable, and 3) Pteridophyta Herbarium media was effective to be applied in Plantae learning with students’ result completeness ≥75%.